2021
DOI: 10.1002/ecs2.3652
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeepers of transformation: private landowners evaluate invasives based on impacts to ecosystem services

Abstract: Gatekeepers of transformation: private landowners evaluate invasives based on impacts to ecosystem services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Rajala et al (2021) highlight the difficulty of convincing producers to manage Kentucky bluegrass on their land. Rajala et al (2021) showed that many producers within North Dakota tend to be reactive rather than proactive and may delay intervention until factors affecting their operation have shifted negatively. These data and models provide a glimpse into future scenarios, which allow producers to be more proactive in dealing with an invasion of bluegrass and projected changes in climate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Rajala et al (2021) highlight the difficulty of convincing producers to manage Kentucky bluegrass on their land. Rajala et al (2021) showed that many producers within North Dakota tend to be reactive rather than proactive and may delay intervention until factors affecting their operation have shifted negatively. These data and models provide a glimpse into future scenarios, which allow producers to be more proactive in dealing with an invasion of bluegrass and projected changes in climate.…”
Section: Resultsmentioning
confidence: 99%
“…Rajala et al (2021) surveyed North Dakota landowners' acceptance of Kentucky bluegrass, the effects of an invasive grass on ecosystem services, and landowner management intention to reduce or control the species and reported that landowners appear to be reactive, rather than proactive in managing Kentucky bluegrass. Rajala et al (2021) report that ecological losses may need to be severe before landowners attempt to reduce or control Kentucky bluegrass. This high threshold for behavioural change on the part of land managers highlights the need for providing early diagnosis of potential forage shortages.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations